Bridging food security and consumer communities through urban agro-architecture assessing household vegetable consumption in medium cost residential communities of Buhangin and Talomo Districts, Davao City - Camahalan, Alden Gene Adrian C. (2019)
With the current pressing issue of poor food security especially in urban and suburban areas, and even with the Philippines as a major agricultural producer in Asia, the need to address food shortages and poor food access and availability is higher. Emergence of strategies such as Urban Organic Agriculture and Landscaping are projected to provide the solution to the issues as well as improve the state of food security, such as the Gulayan sa Barangay encouraged by the Local Government of Davao City. The study aimed to bridge food demand, especially that of vegetable crops, and consumers by developing the ideal space allocation and arrangement in the design and zoning of a residential community that incorporates Urban Vegetable Gardening practices. Through identifying the commonly consumed vegetable crops and the amount consumed monthly (demand) by 100 randomly-selected households in selected Residential Subdivisions in Buhangin and Talomo, Davao City, the study arrived with the result of a minimum of 23.2 square meters, as the amount of land/space needed to accommodate the monthly vegetable crop demands of a single household. The area of land/space was proposed to be integrated into the Residential Subdivision, in both its site and lot zoning and design of its housing units and other buildings